The modern American military - Kennedy, David M. (Oxford University Press, 2013)
The advent of the all-volunteer force and the evolving nature of modern warfare have transformed our military, changing it in serious if subtle ways that few Americans are aware of. Edited by Pulitzer Prize-winning historian David M. Kennedy, this stimulating volume brings together insights from a remarkable group of scholars, who shed important new light on the changes effecting today's armed forces. Beginning with a Foreword by former Secretary of Defense William J. Perry, the contributors take an historical approach as they explore the ever-changing strategic, political, and fiscal contexts.